Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Mid-Chapter Check Point - Page 71: 4



Work Step by Step

Factor each radicand so that one of the factors is a perfect square to obtain: $=3\sqrt{4(3)} - \sqrt{9(3)} \\=3\sqrt{2^2(3)} - \sqrt{3^2(3)}$ Simplify each radical to obtain: $=3\cdot 2\sqrt{3} - 3\sqrt{3} \\=6\sqrt{3} - 3\sqrt{3}$ Factor out $\sqrt{3}$ to obtain: $=\sqrt{3}(6-3) \\=\sqrt{3} \cdot 3 \\=3\sqrt{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.